Willingness of receiving preventive treatment and its determinants among individuals with latent tuberculosis infection in Shenzhen, China - Jin Wang; Xiaoliang Zha; Qiu Zhang; Moru Chen; He Zhang; Feng Ding; Jianfeng Zeng; Tantan Ren; Ye Chen; Shuihua Lu; Xiangxiang Liu (BMC Infectious Diseases)
Abstract Background The study aimed to assess the willingness of receiving tuberculosis preventive treatment (TPT) and identify influence factors on their decisions among individuals with latent tuberculosis infection (LTBI). Methods Individuals diagnosed with LTBI at a designated tuberculosis (TB) hospital were recruited from July 2023 to June 2024. Data on socio-demographic characteristics, knowledge of TB, the decision to receive TPT along with the underlying reasons were collected using electronic questionnaires. Binary logistic regression analysis was employed to identify independent factors associated with the willingness of receiving TPT. A P value less than 0.05 was considered statistically significant. Results A total of 317 individuals with LTBI were included in this study. Among them, 254 (80.13%) expressed a willingness to receive TPT, while 63 declined. Of those 254, 58 (22.83%) ultimately refused treatment. Gender (P < 0.05; OR = 1.983; 95% CI:1.052–3.738), educational level (P < 0.01; OR = 3.489; 95% CI:1.524–7.985) and knowledge of TB (P < 0.05; OR = 3.688; 95% CI:1.835–16.278) were significantly associated with willingness to receive TPT. The top three reasons for willingness to receive TPT were: concern about developing active tuberculosis (ATB), reducing the risk and severity of ATB, and doctor’s recommendation, accounting for 69.09%, 46.69%, and 42.90%, respectively. The top four reasons for refusal TPT included: fear of adverse drug reactions, perceived low risk of developing ATB, fear of adverse drug events and uncertainty about the effectiveness of TPT, accounting for 9.46%, 6.94%, 4.73%, and 4.73%, respectively. Conclusions TPT acceptance remained suboptimal and was influenced by gender, education level and TB knowledge. Improving LTBI patient and health care provider education on TB risks and TPT benefits could enhance adherence. Clinical trial number Not applicable.